2017
DOI: 10.1002/hep.28851
|View full text |Cite
|
Sign up to set email alerts
|

The dendritic cell–T helper 17–macrophage axis controls cholangiocyte injury and disease progression in murine and human biliary atresia

Abstract: Biliary atresia is a fibroinflammatory obstruction of the extrahepatic biliary tree in neonates. While intrahepatic bile duct proliferation is universal at diagnosis, bile duct paucity develops later. We hypothesized that polarized T helper lymphocyte responses orchestrate progression of intrahepatic biliary injury in this disease. IL-17A-GFP, CD11c/DTR and IL17RA−/− mice were used to examine T-lymphocyte polarization, inflammatory leukocyte recruitment and biliary injury in rhesus-rotavirus induced biliary at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 28 publications
2
35
1
Order By: Relevance
“…Despite a prominent type 1 inflammatory response, studies in humans and mice also show a Th17 commitment and its correlation with disease progression . In addition, livers and sera from a subgroup of BA patients have high levels of type 2 cytokines, such as IL‐13, IL‐33, and IL‐4 .…”
Section: Basic Researchmentioning
confidence: 99%
“…Despite a prominent type 1 inflammatory response, studies in humans and mice also show a Th17 commitment and its correlation with disease progression . In addition, livers and sera from a subgroup of BA patients have high levels of type 2 cytokines, such as IL‐13, IL‐33, and IL‐4 .…”
Section: Basic Researchmentioning
confidence: 99%
“…Among all viruses, rhesus rotavirus type A (RRV) is the gold standard to model BA in mice. The use of this murine model has facilitated the study of different aspects of the disease, such as the underlying mechanisms of the pathogenesis (26)(27)(28)(46)(47)(48)(49)(50) or the identification of novel therapeutic targets (51). This experimental form of BA uses BALB/c newborn mice that, when challenged with RRV within the first hours of life (12-48 h), can recapitulate many aspects of human BA (52) such as time-restricted susceptibility to the viral infection, portal tract infiltration of inflammatory cells and obstruction of both extrahepatic and intrahepatic biliary tree (5,34).…”
Section: Rhesus Rotavirus-induced Murine Modelmentioning
confidence: 99%
“…In this study, a model of biliary injury perpetuation was proposed in which IL-17A stimulated cholangiocytes to produce C-C motif chemokine ligand 2 (CCL2) that recruited inflammatory macrophages expressing IL-17AR to target the epithelium (51), as shown in Figure 4B. In this model, depletion of Th17 cells or blockage of CCL2 prevented bile duct paucity and the number of Th17 cells correlated with the concentration of gamma glutamyl transpeptidase (GGT), a biochemical marker of bile duct injury (51). In BA patients, the presence of Th17 in the biliary tree and peripheral blood has been confirmed, as well as Th17-related markers in liver tissue [IL-17A and retinoic acid-related orphan receptor (ROR)-γt] and serum IL-23.…”
Section: Mechanisms Of Post-obstruction: Chronic Inflammation Duct Pmentioning
confidence: 99%
“…Furthermore, liver tissue from BA patients at diagnosis had significantly increased levels of IL-17 mRNA [77]. Lages et al showed that CD4+ T cells were primarily responsible for IL-17 production and IL-17 stimulated macrophage influx and biliary injury in the mouse model [78]. Analysis of human tissue reveals that high expression of IL-17 producing T cells was associated with need for liver transplant.…”
Section: T-cell Immunitymentioning
confidence: 99%